Effect of pinch types on pinch force sense in healthy adults - Lin Li; YanXia Li; Peng Jia; Shuyan Wang; Wanpeng Wang; Yuxiang Liu (Frontiers in Human Neuroscience, 2022)
Pinch force sense plays an important role in the performance of daily finger movements, including tip, key, palmar pinch. The present study investigated the roles of pinch type in the sensation of pinch force among healthy participants in the ipsilateral force reproduction trial. This study instructed forty healthy adult subjects (20 women and 20 men) in producing reference forces at different levels [10, 30, 50% maximal voluntary isometric contraction (MVIC)] by adopting 3 pinch types (tip, key, and palmar pinches) and in reproducing the above force levels with the identical hand. Our study revealed that subjects are significantly more sensitive detecting alterations of pinching forces with tip pinch but not key or palmar pinch under high forces (30 and 50% MVIC) but not at lower force levels (10% MVIC).